Scalable room-temperature dielectric switchable composites with giant contrast ratio and great cycle stability. (December 2022) - Gong, Yutie; Li, Zhenzhen; Li, Hairong; Zhou, Weijie; Zhao, Jiayu; Pei, Xianglin; Jiang, Ming; Gong, Wei
Abstract: Room-temperature dielectric switching materials are highly desirable for many potential industrial applications in smart electronic/electrical engineering fields, but they suffer from key limitation of poor integration of remarkable dielectric switching properties, promising scalability, and low cost. Here, a general solution to solve this problem is demonstrated to attain an excellent cost/performance balance. By mixing ionic liquids (ILs) with polyethylene glycol (PEG), an all-organic composite enables an ultrahigh dielectric switching ratio above 320.6 at 34.2 Hz, almost 100% dielectric constant retention after 500 cycles, the highest attainable to a ∼35 °C wide thermal hysteresis loop, and tunable dielectric transition temperature. Also, the PEG/ILs can defeat the conflict of dielectric switching properties versus cost, namely impressive dielectric switching properties are achieved through simple mixing of commercialized components without solvent. The findings offer promise for highly efficient, scalable, low-cost, and environmentally friendly preparation of high-performance room-temperature dielectric switching materials. Graphical abstract: Image 1 Highlights: PEG/ILs composites are achieved through simple mixing of commercialized components without solvent. PEG/ILs enable a dielectric switching ratio above 320.6 and almost 100% dielectric constant retention after 500 cycles. PEG/ILs exhibit a ∼35 °C wide thermal hysteresis loop and tunable dielectric transition temperature. PEG/ILs composites attain an excellent cost/performance balance and promising scalability.